Development of Song-Assisted Virtual Reality-Based BioPulse Learning Media to Improve Learning Outcomes of Human Circulatory System Materials - Fahrizal Husni Maulana; Putri Yanuarita Sutikno (Jurnal Pijar MIPA, 2026)
The low understanding of students of abstract science subjects, especially the human circulatory system, is due to the fact that the learning process is still dominated by lecture methods and the use of textbooks, so that students are less actively involved. This study aims to develop and test the effectiveness of song-assisted virtual reality-based BioPulse learning media in improving the learning outcomes of grade V students on the human circulatory system material. This research uses the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The subject of this study is grade V students at SD Negeri Mulyosari, totalling 31 students. The trial was carried out in two stages, namely a small-scale test involving 9 students and a large-scale test involving 22 students. Data collection was carried out through validation by media experts and experts in learning outcome test materials, in the form of pretests and posttests, as well as questionnaires on teacher and student responses to BioPulse learning media. Data analysis was carried out using normality tests, paired-samples t-tests, and N-Gain tests. The results of the study showed that the BioPulse media developed obtained validation scores of 93.3% for media experts and 91.6% for material experts, indicating a very feasible category. The average student pretest score of 45.4 increased to 87.9 in the posttest. The results of the paired-samples t-test showed a significance value of 0.000 (< 0.05), indicating a significant difference between the values before and after media use.  The N-gain is 0.79, which is in the high category. Teachers' and students' responses to the media are in the very decent category. The song-assisted, virtual reality-based BioPulse learning media was found to be valid and effective in improving student learning outcomes in human circulatory system material in elementary schools.